Avaliação de parâmetros clínicos (dor, edema e trismo) e qualidade de vida em cirurgias de terceiros molares mandibulares sob diferentes estratégias de analgesia preemptiva: revisão sistemática e ensaio clínico randomizado - Cetira Filho, Edson Luiz (2021)
In the last years, clinical trials involving different preemptive analgesia (PA) protocols in surgeries for the removal of lower third molars have mainly investigated clinical parameters, with few studies evaluating pharmacological strategies associated or not with photobiomodulation with low intensity laser therapy (LLT). Therefore, this dissertation has two chapters that aimed, respectively: 1) to carry out a systematic review with meta-analysis of primary studies to investigate the effectiveness of PA with non-steroidal anti-inflammatory drugs (NSAID) on inflammatory events (pain, edema, and trismus) postoperative in mandibular third molar surgeries; 2) to evaluate clinical parameters and quality of life in patients undergoing surgical removal of mandibular third molars under different PA strategies. In chapter 1, a systematic review registered on the PROSPERO platform under the number CRD42019128579 was carried out according to the recommendations of the PRISMA guide. Of a total of 2,903 articles, 31 (n = 2,184 patients) were selected. All studies had a low risk of bias but showed high methodological heterogeneity. The PA in the removal of third molars reduced pain scores, especially in the first six hours (n = 151, p <0.001, 95% CI = -2.81 to -0.97). In summary, most NSAIDs show good results for the control of inflammatory events, with reduced pain scores and reduced mean consumption of rescue medication. However, more homogeneous and well-designed clinical studies are needed to determine a possible association between NSAIDs and the effectiveness of treatment for inflammatory events. In chapter 2, a randomized, bifactorial, triple-blind, controlled, randomized, split-mouth clinical trial was conducted with volunteers who required bilateral removal of the third mandibular molars. Forty individuals were randomized and allocated to receive, 1 hour before surgery, 100mg nimesulide or placebo, with LLT subgroups. Clinical outcomes (pain, edema, and trismus) and impact on the quality of life (OHIP-14) were evaluated. The pain peaks occurred 6 hours after surgery in the placebo group and after 8 hours in the nimesulide group. In the placebo group, the use of LLT provided mean pain scores significantly lower than the subgroup without LLT after 4 hours (p = 0.009) and 6 hours (p = 0.048) of extraction. In the nimesulide group, the multifactorial analysis demonstrated that this NSAID, regardless of the use or not of LLT (p = 0.065), significantly reduced the mean pain scores after 4 hours (p = 0.045). As for edema, the Ang-Ceo measure showed a lower value after seven days (p = 0.037) and a lesser cumulative effect (p = 0.036) in the placebo group associated with the use of LLT. In 13 addition, a multifactorial statistical analysis showed a direct effect of the LLT (p = 0.047) on the reduction of the mean scores of global dissatisfactions with quality of life regardless of the association with nimesulide (p = 0.519) after seven days. It was concluded that the preemptive use of nimesulide only delayed the peak of pain. The LLT reduced edema and trismus, and contributed to a better assessment of quality of life. The benefit of the association of both strategies was not superior to the isolated use of LLT.